2001
DOI: 10.1080/15287390152543690
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Status and Lipid Peroxidation in Colorectal Cancer

Abstract: Colon carcinogenesis is a multistep process where oxygen radicals were found to enhance carcinogenesis at all stages: initiation, promotion, and progression. Since insufficient capacity of protective antioxidant system can result in cancer, the aim of this study was to examine the activity of antioxidant enzymes (superoxide dismutase, catalase, glutathione peroxidase, and glutathione reductase) and the levels of reduced glutathione, vitamin C, and vitamin E. The lipid peroxidation products were also determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
68
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(77 citation statements)
references
References 30 publications
9
68
0
Order By: Relevance
“…This may explain the observation of decrease in MDA Jin erythrocytes in our subset of patients. Skrzydlewska et al have reported increased activity of superoxide dismutase, glutathione peroxidase and glutathione reductase (enzymatic oxidant defence system) and a decrease in GSH content (non-enzymatic antioxidant parameter) in cancer tissue suggesting an increased defence against oxidant damage in cancer (14). However MDA levels have been reported to be higher in patients with malignant breast tumor (15, *p < 0.0001 compared to controls **p = 0.05 compared to controls.…”
Section: Resultsmentioning
confidence: 94%
“…This may explain the observation of decrease in MDA Jin erythrocytes in our subset of patients. Skrzydlewska et al have reported increased activity of superoxide dismutase, glutathione peroxidase and glutathione reductase (enzymatic oxidant defence system) and a decrease in GSH content (non-enzymatic antioxidant parameter) in cancer tissue suggesting an increased defence against oxidant damage in cancer (14). However MDA levels have been reported to be higher in patients with malignant breast tumor (15, *p < 0.0001 compared to controls **p = 0.05 compared to controls.…”
Section: Resultsmentioning
confidence: 94%
“…Dursun et al (43) and Skrzydlewska et al (44) observed a significant decrease in CAT in patients with esophageal, gastric and colorectal cancer. Additionally, Chung-man Ho et al (45) noted that the same trend in CAT was correlated with an increase in MnSOD in lung cancer, which confirmed the presence of a synergism between the two enzymes in antioxidant defense mechanisms (24,26).…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in TGFb1 has been correlated with an increase in carcinogenesis progression. 51 On the other hand, some studies have demonstrated increased HNE levels in cancer tissues, 25,52,53 and the HNE-adduct levels seem to be positively correlated to progression in both the grade of malignancy in brain cancers 54 and the stages of hepatitis. 55 Several hypotheses can be formulated to explain these divergences.…”
Section: Hne and Diseases Associated With Oxidative Damage: Links To mentioning
confidence: 99%
“…Oxidized-LDL bound to HNE-adducted apoB has a lower affinity for the apoB/E receptors that are expressed in most cell lines, except macrophages. Such modified LDLs are then reoriented toward scavenger receptors, expressed at the surface of macrophages and smooth muscle cells, leading to the Low levels of HNE in tumor tissues compared with healthy tissues, rTGFb1 [46][47][48]49 High levels of HNE in cancer tissues [50][51][52][53][54][55] Luminal HNE triggers the positive selection of preneoplastic cells in colorectal cancer 14,59 Atherosclerosis 37 The subsequent atheromatous plaque formation involves macrophage infiltration and activation of smooth muscle cells leading to fibrogenesis. HNE can particularly form adducts with PDGFR (platelet-derived growth factor receptor) in atherosclerotic aortas and the use of the antioxidant hydralazine prevents HNE-related adduction and slows the progression of the disease.…”
Section: Hne and Diseases Associated With Oxidative Damage: Links To mentioning
confidence: 99%